Glencoe literature : the reader's choice. Course 4 - Chin, Beverly Ann.; Wolfe, Denny.; Copeland, Jeffrey.; Dudzinski, Mary Ann.; Ray, William.; Royster, Jacqueline Jones.; Wilhelm, Jeffrey. (Glencoe/McGraw-Hill, 2002)
The short story; Nonfiction; Poetry; Drama; Epic; Science fiction and fantasy.